ANALYSIS OF HUMAN CAPITAL MANAGEMENT IN THE MSME TOURIST ACCOMMODATION SECTOR IN INDONESIA - Ari Widi Prakasa; Aries Setiawan (Sean Institute, 2023)
The purpose of this study is to investigate the ways in which small and medium-sized tourism accommodations in Indonesia manage their human resources. This study is an analysis of the human capital management difficulties that are associated with MSME tourist accommodation in Indonesia. It gathers the most relevant contributions from the most important works that have been done on the subject. It also derives conclusions to establish the conditions under which it can be called a strategic management of human and intellectual resources. These conditions are determined by the circumstances. In addition to the training and development of employees and their managers, job security, and ownership structures, a qualitative approach with descriptive study of numerous essential aspects of human resource management was carried out.